Active Drug Targeting of a Folate‐Based Cyclodextrin–Doxorubicin Conjugate and the Cytotoxic Effect on Drug‐Resistant Mammary Tumor Cells In Vitro. Issue 9 (4th May 2015) - Mizusako, Hideki; Tagami, Tatsuaki; Hattori, Kenjiro; Ozeki, Tetsuya; Donovan, Maureen D.; Langguth, Peter; Polli, James E.; Tamai, Ikumi; Vig, Balvinder; Yu, Lawrence X.
<x xml:space="preserve">Abstract</x> Active drug targeting is an effective therapeutic approach for the treatment of malignant cancers and novel types of drug carriers have been developed. In this study, we developed a cyclodextrin (CD)‐based novel carrier–drug conjugate, called per‐FOL‐β‐CD‐ss‐DOX, which has folic acid (FA) molecules at the end of primary hydroxyl groups of β‐CD and a pH‐cleavable spacer with an anticancer drug, doxorubicin (DOX), at the end of secondary hydroxyl groups. This per‐FOL‐β‐CD‐ss‐DOX exhibited a significant cellular uptake as compared with the free DOX solution by EMT6/P cells, which activate the expression of folate receptor (FR). Cellular uptake of per‐FOL‐β‐CD‐ss‐DOX was significantly inhibited in the presence of FA and was also inhibited at 4°C. The conjugate exhibited remarkable cytotoxic effects in EMT6/AR1 cells, which are resistant to DOX, whereas free DOX solution did not exhibit this effect. These results suggest that per‐FOL‐β‐CD‐ss‐DOX can be taken up into cells via FR‐related endocytosis and the cleaved DOX derived from it in endosomes could escape the efflux caused by P‐glycoprotein, resulting in the cytotoxic effect. Therefore, the drug delivery by per‐FOL‐β‐CD‐ss‐DOX may be a useful approach for drug delivery to FR‐expressing cells such as drug‐resistant malignant cancers. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2934–2940, 2015